YIELD AND YIELD COMPONENTS OF MAIZE (ZEA MAYS L.) VARIETIES AS INFLUENCED BY PLANT POPULATION AND TIME OF NITROGEN SECOND DOSE APPLICATION IN GUINEA SAVANNAH OF NIGERIA - Ladan, Muhammad K.; Muhammad, Abdulhadi; Jari, Sanusi (FUDMA JOURNAL OF SCIENCES, 2025)
The Study was carried out simultaneously at two location namely; Institute for Agricultural Research IAR, A.B.U., Samaru- Zaria (11011’N 07038E and 686m above sea level) and College of Agriculture and Animal Science, Farm Mando, Kaduna (Lat 10o43’N, Long 06o34’E 500m above sea level) both located in the Northern Guinea Savannah Ecological Zone of Nigeria respectively during 2023/2024 cropping season, to evaluate the effect of plant population and time of nitrogen second dose application on yield and yield attributes of three maize varieties in Nigerian savannah. Treatments consisted of Three maize varieties; SAMMAZ 15, SAMMAZ 16, and SAMMAZ 17, three plant populations levels; P1 (40,000 plants ha-1), P2 (60,000 plants ha-1) and P3 (80,000 plants ha-1) and five times of nitrogen second dose application; 4, 5, 6, 7 and 8 weeks after sowing (WAS). Treatment were factorially combined in a randomized complete block design (RCBD) and replicated three times. Data on yield parameters collected were number of cobs plant-1, number of kernels pod-1,cob length, cob diameter and kernel yield kg ha-1. Results showed that 60,000 plants ha-1had the best performance on yield parameters and gave the highest maize yield kg ha-1, followed by 40,000 plants ha-1 and 80,000 plants ha-1 respectively. Second dose of nitrogen application at 6 WAS resulted in higher growth attributes and gave the highest grain yield kg ha-1 over other timings evaluated and SAMMAZ 16 outperformed the other varieties in terms of yield attributes and gave the highest grain yield in kg ha-1. The study recommends that...
Keywords: Maize; Nigerian Savannah; Plant population; Time of nitrogen second dose application; Variety; Yield